Establishing reliability in notational analysis of soccer of Malaysia - Mohamad Razali Abdullah; Mainul Haque; Rabiu Muazu Musa; Norlaila Azura Kosni; Ahmad Bisyri Husin Musawi Maliki; Pathmanathan K. Suppiah (IJPSRR, 2017)
Numerous methods of notational analysis are been used in performance analysis of soccer to provide coaches and players with information on their performance. Creating reliability for notational analysis in soccer is necessary for the information to be relied upon. Nevertheless, most performance analysts seldom report the reliability of their analysis assuming that the present of performance parameters could reflect the reliability of their analysis. The purpose of this study is to establish reliability in the notational analysis of soccer. Performance indicators associated with the demand for the game were identified, operationalized and installed on tablet application. Eleven performance analysts were provided with eleven tablets set up with Stat watch application and instructed to analyse the performance of a particular player during a soccer match based on the performance indicators. Cronbach’s alpha and Cohen’s Kappa reliability testing was employed to test the consistency as well the level of agreement between the performance analysts at P ≤ 0.05 level of confidence. The result shows α=0.90 and K=0.89 (0.10, 95%), P < 0.001, respectively which suggested a high consistency of their measurement and indicated that the agreement between the performance analysts on their analysis was perfect and far beyond chance. Reliability in the notational analysis of soccer using tablet application could be achieved.